Analisis Perlindungan Hak Asasi Manusia dalam Tatanan Hukum Indonesia - Ayu Azkiah; Suhayib Suhayib; Rafi Reno Fetra (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
The rapid use of the internet among junior high school (SMP) students increases the risk of digital crime, especially phishing. This community service activity aims to strengthen digital literacy and cybersecurity awareness of SMP Negeri 3 students in Sorong City, Southwest Papua. The program is carried out by the Victory Sorong University team through five systematic stages, namely socialization, training, technology application, evaluation, and program sustainability. Interactive methods were used to increase student engagement, including participatory lectures, phishing case simulations, ROT13 encryption practices, two-factor authentication demonstrations, and technology-themed educational chain sentence games. The results showed a significant improvement in students' ability to identify the characteristics of phishing and understand its prevention measures. A game-based learning approach has proven effective in building students' active engagement as well as strengthening basic cybersecurity competencies. This activity has a positive impact in the form of increasing digital literacy, forming safe internet habits, and collective awareness of cyber threats. Thus, this program can be used as a model of continuous education to strengthen the culture of digital security among junior high school students.